Parental Depression Predicts Child Body Mass via Parental Support Provision, Child Support Receipt, and Child Physical Activity: Findings From Parent/Caregiver–Child Dyads - Zarychta, Karolina; Banik, Anna; Kulis, Ewa; Boberska, Monika; Radtke, Theda; Chan, Carina K. Y.; Luszczynska, Aleksandra (Frontiers in Psychology, 2020)
Objective: Although there is substantial evidence corroborating the within-individual associations between depression, social support, moderate-to-vigorous physical activity (MVPA), and body mass, much less is known about across-individual associations. This study investigated the indirect associations between parental depression and objectively measured body mass in children. In particular, it was hypothesized that higher levels of parental depression (measured at Time 1, T1), would explain higher levels of child body mass in children (assessed at Time 2, T2), via three mediators, namely parental reports of provision of MVPA support (T1), child reports of receipt of MVPA support (T1), and child MVPA (T2). Design: Parent-child dyads provided self-reports twice, at the baseline (T1) and 7- to 8-month follow-up (T2). A total of 879 dyads were enrolled (1,758 individuals; 5- to 11-year-old children, 52.4% girls, 83.2% mothers). Body weight and height were measured objectively. Manifest path analyses were performed to test the indirect effects. Results: Analyses corroborated the assumed indirect effects: high levels of depression in parents (T1) were indirectly associated with high levels of body mass in children (T2), via three mediators: low levels of parental support provision (T1), low levels of child support receipt (T1), and low levels of child MVPA (T2). The alternative models, assuming that either parental support provision or child support receipt can be excluded as the mediators yielded poor model-data fit. The hypothesized mediation effects were corroborated when controlling for the baseline levels of parental and child MVPA and body mass. Conclusion: The findings confirm complex across-individual effects of parental depression on high levels of body mass in children. Parental mental health may contribute to the childhood obesity epidemic.